Students’ positive responses toward homework given by English teachers at vocational high school - Kris Astuti (Journal of English Language and Pedagogy, 2019)
This study aims to find out and describe the students’ positive responses toward homework given by English teachers at grade twelve in SMK Negeri 3 Purworejo in the academic year of 2014/2015. The subject of the research is students of SMK Negeri 3 Purworejo grade twelve in the academic year of 2014/2015. The approach is qualitative naturalistic and the data were taken using open questionnaire. The research finding reveals 21 final categories. From those 21 final categories, there are four main components which are important to be explored further. Those four components are students, homework materials, teachers, and facilities. The positive responses toward homework coming from the students are satisfaction and happiness if they can do it without cheating. They are challenged in doing the homework and get new knowledge. Doing the listening homework trains students to concentrate. They better understand the learning material, develop their self-confidence, and express their ideas and opinions. For homework materials, the students’ positive responses are dominated by the material that students have already learned and have not learned yet. The positive responses based on teachers are the English teachers have to discuss and give scores of the homework. Regarding facilities, the students consider that the school’s facilities should be various and complete to help them do the homework.